A Region of Endless Dispute: An Analysis of Conflict Theory by Lewis A. Coser in the Context of Islam in Kashmir - Sugandi, Rafid; Hakim, Lukmanul; Erasiah, Erasiah (Universitas Islam Negeri Sumatera Utara, 2024)
The purpose of this paper is to explore the causes of conflict and the state of Islamic civilization in Kashmir. The conflict between Pakistan and India in Kashmir is often fought over the Kashmir region, so Kashmir has become an area that is still disputed to this day. This type of research is descriptive qualitative research, namely the analysis and presentation of data in the form of sentences and a deep understanding of what it is. The method used is the historical method with the stages of source collection, source criticism, interpretation and writing. The approach used in this research is the conflict theory of Lewis A. Coser. The result of this research is the conflict between India and Pakistan over Kashmir because of Kashmir's natural resources which are very profitable for the country's economic income, both for India and Pakistan. The prolonged conflict has an impact on the political field, namely Kashmir losing the right to special autonomy and legal guarantees, religion, namely increasing discrimination, economy, namely the decline in the number of tourists, and education, namely the irregular education system.